2016
DOI: 10.1007/s12010-016-2367-2
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosative Stress Response in Vibrio cholerae: Role of S-Nitrosoglutathione Reductase

Abstract: Vibrio cholerae, the causative agent of cholera, poses serious threats to humans worldwide. V. cholerae faces host inflammatory response and encounters nitrosative stress before establishing successful colonization. It is not clear how V. cholerae combats nitric oxide and reactive nitrogen species. In the present study, we used three clinical strains of V. cholerae and tested their nitrosative stress response pattern towards sodium nitroprusside (SNP) and S-Nitrosoglutathione (GSNO). Among them, V. cholerae, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…This reversibility and structural changes caused by oxidation allow signalization cascades to have a fine coordination of adaptive responses to react to endogenous and exogenous metabolic processes (Vázquez-Torres, 2012). Proteins S-nitrosylation is important to a considerable variety of mechanisms, from RNS detoxification in bacteria (Hess et al, 2005;Patra et al, 2016) and protozoa (Wang et al, 2014), to regulating cell cycle in fungi cells (Foster et al, 2009;Lee P.Y. et al, 2011;Majumdar et al, 2012) and regulating human diseases (Chung, 2015;Bradley and Steinert, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This reversibility and structural changes caused by oxidation allow signalization cascades to have a fine coordination of adaptive responses to react to endogenous and exogenous metabolic processes (Vázquez-Torres, 2012). Proteins S-nitrosylation is important to a considerable variety of mechanisms, from RNS detoxification in bacteria (Hess et al, 2005;Patra et al, 2016) and protozoa (Wang et al, 2014), to regulating cell cycle in fungi cells (Foster et al, 2009;Lee P.Y. et al, 2011;Majumdar et al, 2012) and regulating human diseases (Chung, 2015;Bradley and Steinert, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…From these facts, we propose that in a nitrate deprived anaerobic growth condition, in-vivo nitration and de-nitration is a cyclical phenomenon which is governed by controlled oxidative condition of cell and can perform as a sole source of respiration just to keep cells viable. Apart from this, in our previous studies we showed the role of S-nitrosoglutathione Reductase (GSNOR) 21 and Catalases (KatB & KatG) 22 in combating nitrosative stress mediated by GSNO and peroxynitrite respectively. Hence, in-vivo nitration might also be an advanced evolutionary adapted mechanism of nitrosative stress tolerance found in V. cholerae , as it restricts proteome to unnecessary PTN in nitroso-oxidative stress prevailing environment such as inside human gut.…”
Section: Discussionmentioning
confidence: 90%
“…12,[22][23][24]32 Although the exact mechanism for cysteine-responsive transcriptional regulation is so far unknown, conserved cysteines may play an important role in posttranslational modifications. 33 Formaldehyde-responsive transcriptional factors such as formaldehyde activating enzyme (Fae) are found in P. denitrificans and Rhodobacter sphaeroides. 29 However, we were unable to find any such transcriptional factor in M. smegmatis.…”
Section: Discussionmentioning
confidence: 99%